The transformative cognition of English as a Foreign Language student teachers’ personal practical knowledge - Xu, Quan; Wang, Ting (Frontiers in Psychology, 2023)
This study investigates the process by which English as a Foreign Language (EFL) student teachers transmute their Pedagogical Content Knowledge (PCK) into Personal Practical Knowledge (PPK) within a blended learning community. Data sources, including conversation transcripts, reflective journals, and field notes, were meticulously examined utilizing the commonplaces of temporality, sociality, and place. Several key findings were unveiled: (1) The volume and focal points of transformed PPK varied across participants; (2) The metamorphosis of PCK into PPK was found to be selectively partial, filtered by factors such as previous learning experiences, course expectations, and levels of engagement; (3) The selection process was molded within the dynamic interplay of the internal components of the blended learning community and the external socio-cultural conditions. The study concludes that the cognition mechanism of EFL student teachers' PPK is characterized by elements of variation, selection, and dynamism.